Concept Maps and promoting active classroom participation (Research, Society and Development, 2020)
In higher education today, teachers face the challenge of encouraging active student participation in order to promote meaningful learning. Considering this context, this article aims to analyze the use of concept maps as a didactic resource to promote the active participation of students in expository lessons. To meet this goal, we analyze the use of concept maps in a discipline of the Computer Science course at the Federal University of Pampa. Observing the menu and the objectives of the discipline called “Introduction to science and technology”, it is possible to use concept maps in expository lessons and lectures. Thus, we seek to provide the active participation of students, who need to overcome the performance of simple spectators. In this study, it is also intended to verify if the concept maps can be a useful tool for the professor to plan and present the syllabus and objectives of the subject. As a result, some conceptual maps elaborated based on the menu, objectives and expected content for the subject studied are presented.